The art of playful mess : Co-choreographing the early years dance pedagogical practices - Colliander, Tuire (Sage, 2024)
This article presents explorations of co-choreographing the early years dance pedagogical settings through dialogical and intra-active approaches in the context of artistic research. It discusses how to choreograph the pedagogical settings in such a manner, that the distribution of the artistic agency would become more equal, and the complex relational aspects and diversities would have time and space to emerge. The significance and possible consequences of co-choreographing the dances as well as the pedagogical arrangements will be also examined, followed with practical examples of what might the materiality of the space suggest and how to respond to it. The paper presents the Storyboard Method as a drawing-based method created by children for co-creating and writing choreography. It proposes the Storyboard Method having potential to open possibilities for working together with all ages and different linguistic skills in a participant-driven and playful manner. The work also suggests that by deconstructing the adult-child dichotomy and re-distributing the authority of knowledge, for example, through drawing-based playful methods, we could enhance the respectful encounters and allow the messy and complex qualities of creativity to emerge and enrich the artistic work.
Keywords: tanssi; taiteellinen tutkimus; koreografia; pedagogiikka; tanssiteokset